Fire Regimes: Spatial and Temporal Variability and Their Effects on Forests - Sylvie Gauthier (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Fire regimes (occurrence, cycle, severity, size, etc.) are key factors in many forest ecosystems, as they are often critical drivers of forest composition, dynamics, and ecosystem processes. Fire regimes vary in space and time according to climatic, physical and biological factors. A better understanding of the interacting factors controlling fire regimes may contribute to improving fire and forest management and their future projection in the context of global change. Knowledge of how fire regimes affect natural landscapes is also used in forestry as a template to manage the forest for wood production. This approach, keeping biodiversity and ecological processes associated with natural fire regimes, may also help in maintaining forest productivity and resilience in the face of climate change. This Special Issue aims to synthesize current understanding of factors affecting fire regime characteristics, to present recent research on fire regimes and their effects on forest ecosystems, and to illustrate how this knowledge could be translated into forest or fire management strategies in the context of global change.